Axioms of Ecumenical History - Van Dusen, Henry P. (Theology today, 1972)
“Up to the eve of the nineteenth century, hardly a single organized Christian fellowship existed, let alone organization across denominational lines; in contrast, at mid-point in the twentieth century, there are thousands of vigorously functioning agencies of trans-denominational collaboration. In these latter days, the practice of Christians with respect to the unity of Christ's church has begun to accord with their profession. How can we account for this newness, the novelty of the modern movement of Christian unity? What are the underlying causes, the explanation of this amazing, wholly unprecedented reversal of previous practice?”